The use of hybrid scientometric clustering for systematic literature reviews in business and economics - Tim Viergutz; Birgit Schulze-Ehlers (Georg-August-Universität Göttingen, Department für Agrarökonomie und Rurale Entwicklung (DARE), 2018)
Given a substantial increase in publications over the last decades, researchers often face an insurmountable quantity of publications potentially relevant for the own research endeavors. Quantitative approaches can be used to analyze the extant scientific literature (also known as scientometrics), which may help to overcome this information overload. This article introduces a hybrid scientometric method, which is based on semantic and bibliographic indicators, for systematic literature reviews into the business and economics literature. To this end, the article provides a step-by-step analysis of the literature referring to the term "loyalty" in the area of business and economics. The analysis reveals four research discourses associated with loyalty, which can be labeled as: 1. Brand loyalty and customer retention, 2. Economic welfare and market power through loyalty, 3. Understanding of customers and formation of loyalty in services marketing and 4. Organizational and employee loyalty. The understanding and use of loyalty is described for each research discourse. The article closes with a discussion about the overall usefulness of the quantitative approach for the review of latent constructs such as loyalty.
Keywords: 330; loyalty; bibliometric methods; LSA; latent constructs